Proposed policies on palliative care for elderly people in Latin America and the Caribbean - Parodi, Jose F. (2016)
The fast aging of population, epidemiological changes and the need to guarantee human rights (health, social protection, etc.) force countries and the wider community to become aware and develop policies that form the basis for an strategy of maintaining the health and care of elderly people. This should be designed taking into account the particularities of this age group, and the need for adaptation of social health services to provide quality care and equity. The adequacy of services involves recognizing the new requirements, the particularities of the risks and problems of this stage of life, comprehensive care, and even decent evidence-based on the end of life. In the presence of new problems and new goals, new skills, new work scenarios and an information system that improve the efficiency and quality of interventions are required.